Neuropathology in Mouse Models of Mucopolysaccharidosis Type I, IIIA and IIIB - Wilkinson, Fiona L.; Holley, Rebecca J.; Langford-Smith, Kia J.; Badrinath, Soumya; Liao, Aiyin; Langford-Smith, Alex; Cooper, Jonathan D.; Jones, Simon A.; Wraith, J. Ed; Wynn, Rob F.; Merry, Catherine L. R.; Bigger, Brian W. (PLOS ONE, 2012)
Mucopolysaccharide diseases (MPS) are caused by deficiency of glycosaminoglycan (GAG) degrading enzymes, leading to GAG accumulation. Neurodegenerative MPS diseases exhibit cognitive decline, behavioural problems and shortened lifespan. We have characterised neuropathological changes in mouse models of MPSI, IIIA and IIIB to provide a better understanding of these events. Wild-type (WT), MPSI, IIIA and IIIB mouse brains were analysed at 4 and 9 months of age. Quantitative immunohistochemistry showed significantly increased lysosomal compartment, GM2 ganglioside storage, neuroinflammation, decreased and mislocalised synaptic vesicle associated membrane protein, (VAMP2), and decreased post-synaptic protein, Homer-1, in layers II/III-VI of the primary motor, somatosensory and parietal cortex. Total heparan sulphate (HS), was significantly elevated, and abnormally N-, 6-O and 2-O sulphated compared to WT, potentially altering HS-dependent cellular functions. Neuroinflammation was confirmed by significantly increased MCP-1, MIP-1α, IL-1α, using cytometric bead arrays. An overall genotype effect was seen in all parameters tested except for synaptophysin staining, neuronal cell number and cortical thickness which were not significantly different from WT. MPSIIIA and IIIB showed significantly more pronounced pathology than MPSI in lysosomal storage, astrocytosis, microgliosis and the percentage of 2-O sulphation of HS. We also observed significant time progression of all genotypes from 4–9 months in lysosomal storage, astrocytosis, microgliosis and synaptic disorganisation but not GM2 gangliosidosis. Individual genotype*time differences were disparate, with significant progression from 4 to 9 months only seen for MPSIIIB with lysosomal storage, MPSI with astrocytocis and MPSIIIA with microgliosis as well as neuronal loss. Transmission electron microscopy of MPS brains revealed dystrophic axons, axonal storage, and extensive lipid and lysosomal storage. These data lend novel insight to MPS neuropathology, suggesting that MPSIIIA and IIIB have more pronounced neuropathology than MPSI, yet all are still progressive, at least in some aspects of neuropathology, from 4–9 months.